Perception and awareness of the environment school through photographs and documentary production - Moura, Jeani Delgado Paschoal; Paschoal, Wilson Aparecido (Geosaberes; Vol 9 No 17 (2018): Jan - Apr, 2017)
Faced with the perception of situations of discase and non-appreciation of public heritage, actions were carried out to raise awareness of the degraded environment of a college of the public state network of Londrina-Paraná. Produced by students, Photographic records from the observation on the spot on degraded points of the physical space of the school and an documentary was made from an interview with the employee responsible for the maintenance of the school and its equipment, whose work has been repeated for 20 years to maintain the school environment in terms of use, a fact that was unknown by most students. As immediate results of this work, we have managed to dialogue with the school community about the importance of the appreciation of the schools as historical, cultural and social heritage, and reflect on the necessity of collective work and the participation of each in the care of the school environment.
Keywords: Degradação ambiental; Agenda 21; Espaços Públicos; Educação.